Spatial and temporal variation in type 1 diabetes incidence in Western Australia from 1991 to 2010: Increased risk at higher latitudes and over time - Ball, S.; Haynes, A.; Jacoby, P.; Pereira, Gavin; Miller, L.; Bower, C.; Davis, E. (Elsevier Ltd, 2014)
This study analysed spatial and temporal variation in childhood incidence of type 1 diabetes mellitus (T1DM) among Western Australia[U+05F3]s 36 Health Districts from 1991 to 2010. There was a strong latitudinal gradient of 3.5% (95% CI, 0.2-7.2) increased risk of T1DM per degree south of the Equator, as averaged across the range 15-35° south. This pattern is consistent with the hypothesis of vitamin D deficiency at higher latitudes. In addition there was a 2.4% (95% CI, 1.3-3.6) average increase in T1DM incidence per year. These effects could not be explained by population density, socioeconomic status, remoteness or ethnicity.© 2014 Elsevier Ltd.